Importance of the Two Dissimilatory (Nar) Nitrate Reductases in the Growth and Nitrate Reduction of the Methylotrophic Marine Bacterium Methylophaga nitratireducenticrescens JAM1 - Mauffrey, Florian; Martineau, Christine; Villemur, Richard (Frontiers in Microbiology, 2015)
Methylophaga nitratireducenticrescens JAM1 is the only reported Methylophaga species capable of growing under anaerobic conditions with nitrate as electron acceptor. Its genome encodes a truncated denitrification pathway, which includes two nitrate reductases, Nar1 and Nar2; two nitric oxide reductases, Nor1 and Nor2; and one nitrous oxide reductase, Nos; but no nitrite reductase (NirK or NirS). The transcriptome of strain JAM1 cultivated with nitrate and methanol under anaerobic conditions showed the genes for these enzymes were all expressed. We investigated the importance of Nar1 and Nar2 by knocking out narG1, narG2 or both genes. Measurement of the specific growth rate and the specific nitrate reduction rate of the knockout mutants JAM1ΔnarG1 (Nar1) and JAM1ΔnarG2 (Nar2) clearly demonstrated that both Nar systems contributed to the growth of strain JAM1 under anaerobic conditions, but at different levels. The JAM1ΔnarG1 mutant exhibited an important decrease in the nitrate reduction rate that consequently impaired its growth under anaerobic conditions. In JAM1ΔnarG2, the mutation induced a 20-h lag period before nitrate reduction occurred at specific rate similar to that of strain JAM1. The disruption of narG1 did not affect the expression of narG2. However, the expression of the Nar1 system was highly downregulated in the presence of oxygen with the JAM1ΔnarG2 mutant. These results indicated Nar1 is the major nitrate reductase in strain JAM1 but Nar2 appears to regulate the expression of Nar1.